2017
DOI: 10.1038/onc.2016.521
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HULC triggers autophagy via stabilizing Sirt1 and attenuates the chemosensitivity of HCC cells

Abstract: Considerable evidences have shown that autophagy has an important role in tumor chemoresistance. However, it is still unknown whether the lncRNA HULC (highly upregulated in liver cancer) is involved in autophagy and chemoresistance of hepatocellular carcinoma (HCC). In this study, we for the first time demonstrated that treatment with antitumor reagents such as oxaliplatin, 5-fluorouracil and pirarubicin (THP) dramatically induced HULC expression and protective autophagy. Silencing of HULC sensitized HCC cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
278
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(282 citation statements)
references
References 40 publications
3
278
0
1
Order By: Relevance
“…The importance of SIRT1 in hepatic autophagy regulation has been reported in ischemic livers (Biel et al., 2016), hepatocellular cancer (Xiong et al., 2017), and hepatosteatosis (Song et al., 2015). MFN2 plays a central role in autophagy induction in the liver (Biel et al., 2016), skeletal and cardiac muscle (Chen & Dorn, 2013; Sebastián et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of SIRT1 in hepatic autophagy regulation has been reported in ischemic livers (Biel et al., 2016), hepatocellular cancer (Xiong et al., 2017), and hepatosteatosis (Song et al., 2015). MFN2 plays a central role in autophagy induction in the liver (Biel et al., 2016), skeletal and cardiac muscle (Chen & Dorn, 2013; Sebastián et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have emerged as key regulators in cellular development and human diseases through modulating gene expression programs at transcriptional, post-transcriptional and epigenetic levels; for example, Koirala et al revealed that lncRNA AK023948 is a positive regulator of AKT; Xia et al demonstrated that lncRNA HOTAIR promotes metastasis of renal cell carcinoma by upregulating histone H3K27 demethylase JMJD3; Xiong H et al reported that lncRNA HULC triggers autophagy via stabilizing Sirt1 and attenuated the chemosensitivity of HCC cells [16-18]. Targeting lncRNA-based signal pathways might be novel therapy method.…”
Section: Discussionmentioning
confidence: 99%
“…In Panzitt’s et al (2007) study, lncRNA HULC , acting as a post-transcriptional regulator of gene expression, was detected to be highly specific up-regulation in HCC. Moreover, subsequent research has shown that HULC can trigger protective autophagy and attenuate the sensitivity of HCC cells to chemotherapeutic agents (Xiong et al, 2017). Among the four prognostic lncRNAs, RP11-150O12.3 was recognized as an independent predictor of gastric cancer (GC) prognosis (Ren et al, 2016), which also related to survival time of patients with colorectal adenocarcinoma (Zeng et al, 2017).…”
Section: Discussionmentioning
confidence: 99%